Microalgae as a Feedstock for Carbon Capture Technology - Fa'izah Amadia Abdi; Ismi Arnadia Falah (Journal of Green Chemical and Environmental Engineering, 2025)
Microalgae have emerged as a promising feedstock for carbon capture technology due to their high carbon sequestration efficiency and potential applications in bioenergy and bioproducts. This study aims to assess the prospects and implementation of microalgae-based carbon capture and storage (CCS) systems in mitigating climate change. The research involves a comprehensive review of microalgae cultivation methods, carbon capture efficiency, and conversion technologies such as biochar production, biofuel synthesis, and direct carbon sequestration in industrial applications. A systematic literature analysis was conducted to evaluate the effectiveness, scalability, and economic feasibility of microalgae-based solutions in mitigating climate change. The study also evaluates key factors influencing the scalability of microalgae-based systems, including biomass productivity, nutrient requirements, and technological advancements in harvesting and processing. Results indicate that microalgae exhibit high CO₂ absorption capacity and can be integrated into existing carbon capture frameworks with minimal land and resource constraints. Additionally, advancements in biorefinery approaches have enhanced the economic feasibility of microalgae-based negative carbon technologies. However, challenges such as high operational costs, energy-intensive processing, and regulatory barriers remain critical factors affecting large-scale adoption. In conclusion, microalgae offer a viable solution for negative carbon technologies, but their successful implementation requires interdisciplinary collaboration, technological improvements, and supportive policies to enhance efficiency and cost-effectiveness